Acetaldehyde administration induces salsolinol formation in vivo in the dorsal striatum of Aldh2-knockout and C57BL/6N mice. (15th October 2018) - Ito, Asuka; Jamal, Mostofa; Ameno, Kiyoshi; Tanaka, Naoko; Takakura, Ayaka; Kawamoto, Toshihiro; Kitagawa, Kyoko; Nakayama, Keiichi; Matsumoto, Akiko; Miki, Takanori; Kinoshita, Hiroshi
Highlights: AcH increased the formation of striatal salsolinol in Aldh2-KO and WT mice. AcH-induced salsolinol levels were higher in Aldh2-KO mice than WT mice. None of AcH doses nor the subsequent changes in salsolinol levels altered DA or 5-HT. Abstract: Acetaldehyde (AcH) and salsolinol play important roles in the central effects of ethanol. This study aimed to investigate the effect of administration of AcH on dopamine (DA), DA-derived salsolinol and serotonin (5-HT) levels in the dorsal striatum of Aldh2-knockout (Aldh2-KO) and C57BL/6 N (WT) mice. Animals were treated with AcH (50, 100 and 200 mg/kg) intraperitoneally and dialysate levels of DA, 5-HT and salsolinol were determined using in vivo microdialysis coupled with HPLC-ECD. Salsolinol was first detected at 20 min after AcH administration, and reached its peak concentration (WT mice: 0.29 ± 0.22 pg/μl; Aldh2-KO mice: 0.63 ± 0.17 pg/μl) at 25 min in the 200 mg/kg AcH group, before decreasing rapidly and reaching zero at approximately 55–80 min. Treatment with 100 and 200 mg/kg AcH increased levels of salsolinol in both WT and Aldh2-KO mice, with 200 mg/kg AcH inducing a higher level of salsolinol in Aldh2-KO mice than in WT mice. Treatment with 50 mg/kg AcH produced a small increase in salsolinol levels in Aldh2-KO mice, whereas no elevation of salsolinol was detected in WT mice. The increase in salsolinol formation was found to occur a dose-dependent manner in both genotypes. Administration of AcH and the subsequent changes in salsolinol concentrations did not change DA or 5-HT levels in either genotype. Our study suggests that AcH dose-dependently increases the formation of salsolinol in the dorsal striatum of mice, which provides further support for the role of AcH in salsolinol formation in the animal brain.